2018
DOI: 10.1002/da.22875
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous ketamine treatment in anxious versus nonanxious unipolar treatment-resistant depression

Abstract: Objective To examine the effect of high baseline anxiety on response to ketamine versus midazolam (active placebo) in treatment‐resistant depression (TRD). Methods In a multisite, double‐blind, placebo‐controlled trial, 99 subjects with TRD were randomized to one of five arms: a single dose of intravenous ketamine 0.1, 0.2, 0.5, 1.0 mg/kg, or midazolam 0.045 mg/kg. The primary outcome measure was change in the six‐item Hamilton Rating Scale for Depression (HAMD6). A linear mixed effects model was used to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Significant reductions in overall depressive symptom severity, as measured by QIDS-SR 16 scores, were seen in both the anxious-distress and low–anxious distress groups with greater reductions observed in the anxious-distress group.We also observed a significant and sustained reduction in SI with IV ketamine treatment in both the anxious-distress and low–anxious distress groups. Anxiety symptoms also significantly reduced in patients with anxious depression, a finding that aligns with extant studies (Ionescu et al, 2015; Salloum et al, 2019; Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Significant reductions in overall depressive symptom severity, as measured by QIDS-SR 16 scores, were seen in both the anxious-distress and low–anxious distress groups with greater reductions observed in the anxious-distress group.We also observed a significant and sustained reduction in SI with IV ketamine treatment in both the anxious-distress and low–anxious distress groups. Anxiety symptoms also significantly reduced in patients with anxious depression, a finding that aligns with extant studies (Ionescu et al, 2015; Salloum et al, 2019; Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Ketamine is an N-methyl-D-aspartate receptor antagonist shown to provide rapid antidepressant effects in patients with TRD (aan het Rot et al, 2010; Coyle and Laws, 2015; Feifel et al, 2017; Murrough et al, 2013; Phillips et al, 2019). Moreover, available evidence from controlled clinical trials suggests that ketamine is effective in treating symptoms of anxiety as well as anxious depression (Ionescu et al, 2015; Salloum et al, 2019). However, it has been reported that patients who enroll in clinical trials may not be representative of persons receiving care in clinical practice (Lorenzo-Luaces et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It derived from phencyclidine (PCP) and is designed to alleviate the serious psychosis/psychotic side effects and potential abuse of maternal drugs 2. In recent years, ketamine has been found to have potential therapeutic uses in pain management, neurology, and psychiatry 36. Low-dose intravenous ketamine can reduce perioperative opioid consumption and can provide chronic postsurgical pain relief for patients 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…112 However, a recent study found no difference in the response to ketamine infusion between patients with anxious and non-anxious depression. 113 More research on the predictors of ketamine treatment response in patients with MDD is still needed.…”
Section: Predictor Of Response To Ketaminementioning
confidence: 99%